Sleep, little one, sleep - Bauer, Marion Dane.; McAllister Stammen, Jo Ellen (New York : Simon & Schuster Books for Young Readers, 1999)
Sleepiness is compared to the actions of a spider, a mouse, a bird, and increasingly larger animals.
4.0
K-3
K-3
School Library Journal
Publisher's Weekly
Booklist
Keywords: Animals -- Infancy -- Fiction; Bedtime -- Fiction; Animal babies -- Fiction; Bedtime -- Fiction